Effects of dietary vitamin A restriction on color shelf-life, lipid oxidation, and sensory traits of Longissimus lumborum and Triceps brachii steaks from early and traditionally weaned calves - Daniel, Melissa Jean (Kansas State University, 2007)
Vitamin A (VA) restriction during finishing has been shown to increase marbling in cattle. However, little work has been done to look at the effects that VA restriction might have on color shelf-life and sensory traits of beef. This study involved 48 calves either early-weaned at 137 + 26 d or traditionally-weaned at 199 + 26 d and supplemented with either 15,400 IU/kg dry matter of VA or restricted to no supplemental VA during the finishing phase. Cattle were harvested in two groups, and carcass data were obtained after chilling. Strip loins and shoulder clods were retrieved, vacuum packaged, and cut into steaks after 14 d of aging. Visual and instrumental color scores for 7 d of retail display, thiobarbituric acid reactive substances (TBARS) values, trained sensory panel scores, and Warner-Bratzler shear force (WBSF) values were obtained. The only differences associated with weaning group were that L* values were lower (P < 0.05) on d 4 to 6 for Triceps brachii (TB) steaks from traditionally-weaned calves restricted in VA than early-weaned calves supplemented with high VA. Both Longissimus lumborum (LL) and TB steaks from calves supplemented with high VA had darker, more tan (P < 0.05) color scores after 4 d of display in PVC packaging than steaks from calves restricted in VA. Also, a*, b* and saturation index values were lower (P < 0.05) in LL steaks for the high VA treatment than those from the no supplemental VA treatment. There was less lipid oxidation (P < 0.05), as reported by TBARS, in both muscles from calves restricted in VA than muscles from calves supplemented with high VA. No treatment effects were found for WBSF values for either muscle, and no differences existed in sensory panel traits of the TB steaks. Sensory panel scores were less desirable (P < 0.05) for myofibrillar tenderness and connective tissue amount in LL steaks from calves fed high VA than steaks from calves restricted in VA. Dietary VA restriction during finishing has potential to increase color shelf-life and reduce lipid oxidation, with no negative effects on cooked meat sensory attributes.
Keywords: Early-weaning; Vitamin A; Agriculture, Food Science and Technology (0359)